Inspection model development for production machines based on downtime record - Nur Hazirah Sa'ari (School of Manufacturing , University Malaysia Perlis, 2013)
In the production line, the main objective of the machines to provide the good quality of products at the time given and follow the customer requirement to accomplish customers satisfaction. To reach the objective, the production line should running in smooth flow without or less breakdown. Nevertheless, the real production with the ineffective maintenance strategy becomes barrier to the production to achieving the objective. Reasonably, this problem contributes to high production lost, production defect due to reject product (if the breakdown occurs during the machine is operating) and increasing the maintenance cost. Inspection is one of the Preventive Maintenance (PM) strategies that can be used to reduce machines breakdown problem in the production line